Excitation energy dependence of initial phase shift in Kerr rotation of resident electron spin polarization in a CdTe single quantum well. Issue 2 (2nd February 2017) - Yan, L.‐P.; Takamure, T.; Kaji, R.; Karczewski, G.; Takeyama, S.; Adachi, S.
Abstract: The generation dynamics of a resident electron spin polarization involve the formation and transformation of the associated optically excited states depending on the excitation photon energy. Initial phase shift in the precession of a resident electron spin polarization gives the important clues to reveal the interplay between the associated excited states and resident electrons. In this work, the excitation energy dependence of the initial phase shift in Kerr rotation of a resident electron spin polarization is investigated in a CdTe/Cd 0.85 Mg 0.15 Te single quantum well under a low magnetic field. Through the careful analysis of the spin precession, the excited electron–heavy‐hole pairs show unique spin dynamics when the excitation energy is increasing past the neutral exciton resonance. Meanwhile, the negative initial phase shift becomes significantly large in magnitude. The larger initial phase shift and the unique precession traces are caused by the transformation from neutral excitons to negative trions with accompanying the hole spin‐flip. The exciton‐to‐trion transformation time is estimated experimentally to be ∼ 160 ps.